Study on two-stage economic dispatch of active distribution network with multiple subjects based on electric vehicle grid connection - Zhang, Huaipeng; Tao, Shaoju; Liu, Junfu; Zhou, Weichang (2025 7th International Conference on Information Science, Electrical and Automation Engineering (ISEAE), 2025)
Driven by the concept of green mobility and facing the difficulties brought about by the large-scale access of electric vehicles to the distribution network, this paper proposes a research strategy for the multi-body two-stage economic scheduling of active distribution network based on the grid-connectedness of electric vehicles. Firstly, a dispatchable model of electric vehicle cluster is constructed by using Minkowski sum method; secondly, a mathematical model of gas turbine containing carbon capture is established, and its operation behavior in the process of optimal dispatch is analyzed in depth. In addition, the impact of the uncertainty of new energy generation on the distribution network operation is considered, aiming to maximize the benefits of each participant through optimization. To this end, we construct a two-stage optimal dispatch model of an active distribution network that includes EV access, and use the KKT condition and the dyadic theorem to transform the original model equivalently, and employ the column constraint generation algorithm to solve the model. Finally, the validity and feasibility of the proposed model are verified by the comparative analysis of simulation results.